Strategi Impulse Buying Pada E-Commerce TikTok Shop di Kota Palembang - Zalikha Adelia Putri; Herry Widagdo (Universitas Multi Data Palembang, 2026)
This study aims to analyze the influence of Sales Promotion, Live Streaming, Shopping Lifestyle, Hedonic Shopping Motivation on Impulse Buying in e-commerce TikTok Shop in Palembang City. This study uses a quantitative approach with a survey method through the distribution of questionnaires to respondents spread across 18 sub-districts in Palembang City, with a total of 230 respondents. The sampling technique used is probability sampling with the cluster sampling method. The research data was analyzed using multiple linear analysis with the help of SPSS software version 26. The results of the study show that partially or simultaneously, the four independent variables have a positive and significant effect on variable dependent impulse buying. Thus, the increase in consumers' implied purchases on TikTok Shop can be driven through effective promotional strategies, optimization of live streaming activities, understanding of consumers' shopping lifestyles, and the creation of shopping experiences that provide pleasure and emotional satisfaction.